Development of an Ethno-STEM Learning Module Based on the Acehnese Rapai Geleng Dance - Muhammad Saiful; Mulia Rahmi; Zakiah Zakiah; Hamdi Hamdi; Mariati Mariati (Postgraduate, University of Mataram, 2025)
This research aims to develop a science learning module that is valid, practical, and effective by integrating the Ethno-STEM approach with Acehnese local wisdom, specifically the Rapai Geleng dance. The developed module is intended for junior high school students and focuses on the science topics of vibration, sound, and waves, which are closely related to the rhythmic movements and musical elements of the Rapai Geleng tradition. By embedding local cultural contexts into science learning, the module is designed to provide meaningful and contextual learning experiences for students.This study employed a modified 4D development model consisting of three stages: define, design, and develop. The define stage involved analyzing learning needs, student characteristics, curriculum requirements, learning materials, and learning objectives relevant to Ethno-STEM integration. The design stage focused on structuring the module content, selecting appropriate illustrations and cultural representations, and preparing research instruments, including validation sheets, student response questionnaires, and learning outcome tests. The develop stage involved expert validation, revision based on validators’ feedback, and field testing of the module.The developed module was evaluated through a small-group trial involving 10 seventh-grade students, followed by a class-level trial with 25 seventh-grade students at SMPN 3 Sakti. Data were analyzed using descriptive analysis techniques. Module validity and practicality were determined using percentage calculations, while effectiveness was measured through N-gain analysis based on students’ pretest and posttest results. The findings indicate that the Ethno-STEM-based science learning module achieved a validity score of 81.76%, a practicality score of 92.86%, and an N-gain score of 0.83, which falls into the high category. These results demonstrate that the developed module meets the criteria of being valid, practical, and effective for use in junior high school science learning. The integration of the Rapai Geleng dance into Ethno-STEM learning is therefore recommended as an alternative approach to strengthening culture-based science education and enriching contextual learning resources